(untitled) (Economic and Political Thought, 2019)
In the article, the author shows the true, empirical foundation of Thomas Hobbes’s philosophical and political reflection, justifying his statolatry formulated in Leviathan. In his opinion, Hobbes presents this foundation in the forgotten and seldom analysed treatise Behemoth, being the narration about the events of the English Civil War. In this treatise, Hobbes’s political philosophy meats its social context and history creating the dialectical arrangement consisting of empirical chaos and philosophical order identified as two biblical beasts. For this reason both works should be interpreted as parts of a diptych – the philosophical and empirical lecture clarifying the position taken in Leviathan. The author also shows that in Hobbes’s opinion the true power lies not in physical strength, but in force of ideas, which are the real tool in the fight for power.